2020
DOI: 10.19206/ce-2020-309
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exhaust emission measurements in rural conditions from heavy-duty vehicle

Abstract: Road transport holds for the largest share in the freight transport sector in Europe. This work is carried out by heavy vehicles of various types. It is assumed that, in principle, transport should take place on the main road connections, such as motorways or national roads. Their share in the polish road infrastructure is not dominant. Rural and communal roads roads are the most prevalent. This fact formed the basis of the exhaust emissions and fuel consumption tests of heavy vehicles in real operating condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…41 dm 3 /100 km [44]. In the test presented in Ziółkowski et al [31], the fuel mileage of the investigated vehicle (the same vehicle was used for the investigations of the transport cycle described in this paper) was 30.9 dm 3 /100 km.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 dm 3 /100 km [44]. In the test presented in Ziółkowski et al [31], the fuel mileage of the investigated vehicle (the same vehicle was used for the investigations of the transport cycle described in this paper) was 30.9 dm 3 /100 km.…”
Section: Resultsmentioning
confidence: 99%
“…The investigations have shown that the driving technique has a significant impact on the emission of carbon dioxide, hence the energy consumption. The emission of individual exhaust components and the fuel consumption in a test run of a heavy-duty vehicle under actual operating conditions on roads of different classification have become an increasingly frequent subject of scientific research [29][30][31]. The application of the PEMS equipment allows a detailed assessment of the environmental performance of vehicles and machinery under almost any actual operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Research on exhaust emission measurement methods in the context of changing Euro emission standards is an extremely important and topical issue. Commonly used exhaust emission measurement methods can be divided into those using exhaust gas analysers [33] (including portable emissions measurement system PEMS), analytical methods (e.g. chromatography, spectroscopy) and less popular calculation methods [28].…”
Section: Review Of Exhaust Emission Test Methodsmentioning
confidence: 99%
“…At the present stage of the development of the road transport means, all kinds of activities relating to their impact on the environment play an extremely important role [3]. In this area, a number of legal regulations have been established regarding the conditions of admitting vehicles to roads and a number of control regulations that determine the day-to-day operation of vehicles [4,10]. However, due to the very diversified car fleet and very different conditions of vehicle operation, the existing control regulations do not always effectively and quickly identify vehicles that are operated with faults that endanger their safe operation or exceed the established emission limits.…”
Section: Introductionmentioning
confidence: 99%